Integrating Al-Qur'an translation Texts in the Development of Teaching Materials - Markhamah Markhamah; Atiqa Sabardila; Laili Etika Rahmawati; main Sufanti; Ali Imron Al-Ma’ruf; Indah Prihatin; Hari Kusmanto; Dian Lukiana (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Improving the quality of education needs collaboration between school principals, teachers, and researchers. One form of collaboration is between universities and religious educational bodies such as Aisyiah, Madrasah Ibtidaiyah Muhammadiyah, Madrasah Tsanawiyah Muhammadiyah. The purpose of this activity is to improve the knowledge and skills of teachers in developing teaching materials based on Quran translation text. The methods applied in this activity are lectures, question and answer, assignments/practices, and clinics. The workshop activities were carried out with presentation of material by the resource person to provide knowledge, examples of developing teaching materials, showing the relevance of basic competence, material, and Quran translation text. The activity was continued by carrying out an exercise in the preparation of teaching materials by integrating Quran translation text and a clinic to provide input. The results showed that this activity was beneficial for the participants as they acquire knowledge and skills in developing teaching materials by integrating Quran translation text. Participants get numerous insights and knowledge obtained to be applied in the world of education and teaching - learning process.